Sustainability of Nursing Leadership and Its Contributing Factors in a Developing Economy: A Study in Mongolia - Wang, Bing-Long; Batmunkh, Munkh-Ulzii; Samdandash, Oyunsuren; Divaakhuu, Duumaam; Wong, Wing-Keung (Frontiers in Public Health, 2022)
The sustainability of nursing leadership is a very important problem. Every country continually strives to find the best ways to advance in nurse management and patient care services. Nursing leadership is most desirable in the delivery of health care services. Since there is limited information about leadership skills in Mongolia, to solve the problem of the sustainability of nursing leadership, we carried out this study to explore factors contributing to the sustainability of nursing leadership and their correlation relatively to nurse managers in healthcare institutions. A sample of 205 nurse managers from all forms of health facilities participated in this study. The data were analyzed by descriptive, correlation, and multiple linear regression models using SPSS 19 version. The linear combination of the five independent variables was significantly related to the dependent variable (nurse leadership). Both the behavior and problem-solving are significant regressors of the dependent variable. The correlation analysis significance of the independent study variables, two were found to have a significant effect on nursing leadership: behavior and performance of nurses significantly and positively effect nursing leadership. The transformational role and nurse leadership produced a significantly positive Correlation coefficients give a direction of causation in the relationships of variables, and the multiple linear regression analysis says that two of the variables, namely, behavior and problem-solving, positively contribute to nursing leadership, two of the variables namely, work environment and performance nurse manager do not support; however, variable transformational ability majorly contributes to the sustainability of nursing leadership.